Exploiting a Protocol at network frame to avoid packet failure (International Journal of Engineering and Computer Science, 2015)
The concurrent data communication which depends upon congestion control in internet without packet failure very much difficult ,it straight away signifies an incompetent design to show insecurity and reduced performance. There should some mechanism to control packet lass to avoid quality of services while interpretation media rich content.. Data communication needs major role of network congestion. congestion control algorithm which is the mechanism helps in controlling packet loss which gives good performance of the network. There are many protocols which work as supplement the TCP protocol. These protocol helps to avoid the network congestion. The fair service with open – loop controller built by CSFQ has in progress corrosion in quality as P2P flows conquered internet traffic of late. Token-Based Congestion Control (TBCC) which is the closed loop congestion control was able to limit unbearable resources and give best service to end users. It monitors inter-domain traffic for trust relationships. The new mechanism presents Stable Token-Limited Congestion Control (STLCC). for controlling inter-domain congestion and improve network performance. In this paper we apply the STLCC method